ANALYSIS OF BENEFITS OF JOINT FIELD LECTURE BETWEEN BIOLOGY IAIN KERINCI AND MASTER OF BIOLOGY EDUCATION ON ECOLOGY AND ENVIRONMENT SUBJECT - Razak, Abdul; Sastria, Emayulia; Wahyuni, Wahyuni; Sholichin, Muhamad (Universitas Muhammadiyah Palembang, 2022)
The field lecture is important learning experience for students which is carried out in the open to apply the theory they have learned. This is necessary for the Ecology and Environment subject so that it can provide real experience for students. This study aimed to determine the benefits of joint field lecture between Biology Tadris Study Program at IAIN Kerinci and the Masters in Biology Education at Padang State University for Ecology and Environment subject. The research method was descriptive qualitative-quantitative (mixed method). The research subjects were selected Biology Tadris students along with IAIN Kerinci lecturers and students of the Masters of Biology Education, Padang State University. Data collection was carried out with tools in the form of the questionnaire and the interview list. After the data were collected qualitatively, the data were analyzed based on each indicator of questionnaire and interview, so that the total results of all indicators were obtained. For the data from questionnaire were quantified in percentage. The study results indicated that joint field lecture provided the benefits for students who participated in field lecture activities. The results of questionnaire and interview showed the benefits for students in increasing knowledge, insight, motivation, and experience. In the implementation of the field lecture, students were very good at collaborating, both within groups and among groups. Kuliah lapangan merupakan pengalaman belajar penting bagi mahasiswa yang dilakukan di tempat terbuka untuk mengaplikasikan teori yang telah dipelajari. Hal ini diperlukan untuk mata kuliah Ekologi dan Lingkungan sehingga dapat memberikan pengalaman nyata pada mahasiswa. Penelitian ini bertujuan untuk mengetahui manfaat kuliah lapangan bersama antara Program Studi Tadris Biologi IAIN Kerinci dan Magister Pendidikan Biologi Universitas Negeri Padang pada mata kuliah Ekologi dan Lingkungan. Metode penelitian ini adalah deskriftif kualitatif-kuantitatif (mixed method). Subjek penelitian adalah mahasiswa Tadris Biologi yang terpilih beserta dosen IAIN Kerinci dan mahasiswa Magister Pendidikan Biologi Universitas Negeri Padang. Pengumpulan data melalui kuesioner dan wawancara. Setelah data terkumpul secara kualitatif, data dianalisis berdasarkan masing-masing indikator kuesioner dan wawancara, sehingga diperoleh hasil total dari semua indikator. Untuk data dari kuesioner dikuantifikasi dalam persentase. Hasil penelitian menunjukkan bahwa kuliah lapangan bersama memberikan manfaat bagi mahasiswa yang ikut melakukan kegiatan kuliah lapangan. Hasil kuesioner mahasiswa dan wawancara mahasiswa dan dosen menunjukkan manfaat bagi mahasiswa dalam meningkatkan pengetahuan, wawasan, motivasi, dan pengalaman. Dalam pelaksanaan kuliah lapangan, mahasiswa sangat baik dalam bekerjasama, baik di dalam kelompok maupun antar kelompok.